Partisipasi Masyarakat Dalam Pembangunan Infrastruktur di Desa Cibarusah Kota - Fani Kharismania; Evi Priyanti (Universitas Warmadewa, 2023)
The purpose of this research is to find out the role of the community in infrastructure development in Cibarusah Kota Village, Bekasi Regency, West Java Province. Because in practice, the development process that involves the community mostly has obstacles originating from the participation of the community itself or the performance of the apparatus in coordinating development plans. This research is a type of descriptive qualitative research using data collection techniques, namely observation, interviews and documentation and data analysis techniques through the process of data reduction, data presentation and ends with drawing conclusions after the data is collected. The results obtained from this study are the involvement of the Cibarusah Kota Village community in terms of development, especially the development of village infrastructure, which has played an active role in every stage of its implementation, although overall there are still several obstacles such as differences in perspectives and mindsets between indigenous people and the community. newcomers when conveying aspirations at the assessment stage. But apart from the existing constraints, the cooperation between village officials and the community is well established and harmonious because the shared vision creates positive feedback, although it is still at a low level of sustainability.